The Implementation of Local Wisdom-Based Teaching Material to Increase Students’ Literacy and Numeracy - Hasna Kurnia Putri; Ani Rusilowati; Supriyadi, Supriyadi; Widiyatmoko, Arif; Negoro, Ridho Adi; Teasy, Yoan (Universitas Negeri Semarang, 2025)
This study aims to analyze of the availability of local wisdom-based teaching materials today, the characteristics, validity, readability, effectiveness, and practicality of local wisdom-based teaching materials on the topic of Sound Waves to increasing literacy and numeracy students’. The research design used was called research and development (R&D) with a product trial design using a quasi-experimental design. The research was conducted on students of 11th grade at High School at Bandar Lampung. Data analysis techniques using descriptive, percentages, normalized gains <g>, and t-test. Based on research data analysis, it was found that the results of the literature review using VOSviewer reflect that local wisdom-based education is not only seen as a cultural approach, but has also moved towards integration with 21st century basic competencies. Temporal visualization also shows a shift from a conceptual approach to the development of more applicable learning tools and learning strategies. This condition underlies the development of local wisdom-based teaching materials. The materials significantly improved students’ literacy and numeracy, with the experimental group achieving a high effectiveness category, <g>=0.70, compared to the control group’s low effectiveness, <g>=0.17. Statistical analysis confirmed the significance of the improvement, with the t calculation of 9,41. Practicality tests indicated a very practical rating from teachers (93.5%) and a practical rating from students (84%). The study’s findings indicate that the implementation of local wisdom into teaching materials represents a promising strategy for enhancing student learning outcomes and aligning instructional practices with cultural and educational goals.